2021
DOI: 10.15237/gida.gd21043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carob Extract Supplementation on Chemical and Sensory Properties of Yogurt and Ice Cream

Abstract: In this study, yogurt and ice cream were enriched with carob extract, for giving them functional properties. Three different types of ice cream were produced with three formulations in terms of carob extract concentration. In the first type only carob extract in proportions of 8, 10 and 12% was added to the mixture. The second and third types were different from the first by their aromas: respectively lemon and chocolate. The yogurt samples were produced based on a set type of yogurt procedure. According to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
3
1
0
Order By: Relevance
“…This observation could be mainly attributed to the higher content of total soluble solids in carob molasses. These results are in general agreement with those found by Kulcan et al ( 2021 ). Also, Hassanein et al ( 2014 ) noted that adding concentrated pomegranate extract to yogurt increased its total solids.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This observation could be mainly attributed to the higher content of total soluble solids in carob molasses. These results are in general agreement with those found by Kulcan et al ( 2021 ). Also, Hassanein et al ( 2014 ) noted that adding concentrated pomegranate extract to yogurt increased its total solids.…”
Section: Resultssupporting
confidence: 94%
“…Fermented goat milk (CB4) had the highest TPC throughout the entire storage period, while treatment CB had the lowest TPC content. The current findings are in agreement with Kulcan et al ( 2021 ) who found that the TPC was increased in yoghurt by increasing the added amount of carob extract. Also, Dos Santos et al ( 2017 ) found that the TPC in bio-fermented goat milk has been increased in samples supplemented with grape pomace extract.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For this reason, carob and derived products (powder, syrup, pod) are called functional compounds and are used for enrichment of products (33). Likewise, Kulcan et al (34) reported that total phenolic compounds of yogurt enriched with additional 12% (w/w) carob extract was 643.46 mg GAE/kg-1246.78 mg GAE/kg, respectively. In another study the effect of carob flour (0-4%) on total phenolic content of yogurts was investigated.…”
Section: Total Phenolic Compounds and Antioxidant Activity Of Yogurtsmentioning
confidence: 99%